Pharmacological Study of Schiff Base Derived from Amoxicillin Drug and Vanillin - Huda K. Khassaf (Journal of Global Pharma Technology, 2020)
Objective: Our present investigation is based on development and synthesis for new derivatives of amoxicillin as the wide use of this antibiotic led to serious medical problem of drugs resistance. Methods: Condensation of amoxicillin trihydrate with 4-Hydroxy-3-methoxy benzaldehyde yielded a novel Schiff base derivative of amoxicillin in good yield. Characterization of synthesized compound detected by IR and 1HNMR spectroscopy. The antibacterial activity of new compound was screened against the selected bacteria species Staphylococcus aureus, Escherichia coli, Bacillus cereus, and Klebsella pneumonia. The LD50 value was determinate by using up and down method. Results: Our obtained results for this antibiotic modulation method are within high acceptance criteria in vivo study determination of the toxic effect (LD50) of synthesized compound which was 477.2 mg / kg of body weight give a moderate value. Furthermore, in vitro study included antibacterial activity against some bacteria species of new compound was higher than the respective standard drug at tested doses level. Conclusion: Modulating amoxicillin drug can be used in the management of bacterial resistant disorders. Key words: Amoxicillin, Micro-organism species, Antibacterial activity, Disorders. Schiff-base.